The Law Between Secularism and Theology - Ibnu Amin (NEGREI: Academic Journal of Law and Governance, 2022)
This study aims to describe the legal nature between secularism and theology. The research method used is a literature study with a qualitative descriptive approach using content analytics. The results of the research are secularism and theology is part of the school of natural law (kodrati). Secularism i.e. the rejection of religious thought from life even denies the existence of God from the reality of life whereas the center of life through reason and even secularism can resemble a new religion, hence the law is secular based solely on the will of the people's reason alone. That the legal nature of the theological dimension in the Islamic perspective, namely the narrative based on the revelation of Allah and the Sunnah of the Apostle, shows that a set of rules is extracted from and based on the revelation of the Quran and Sunnah. Law in Islam is seen as having two dimensions, namely Shari'a and fiqh. Sharia is fundamental and absolute values, impossible to change, while jurisprudence is a special field formulated by fuqaha'. Secularism in the sense of rationalism in Islam has always been guided by nash which is like thinking of a mujtahid, so the result is not too far from the truth values that nash teaches. Western rationalism, on the other hand, relies solely on the ability of reason alone, so that it is often found that a law is finally amended again because it is incompatible with the values of justice, good and bad.